2015
DOI: 10.7150/ijms.12742
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the hs-CRP as non-specific biomarker and Alzheimer's disease according to aging process

Abstract: Background: Microglia are involved in immune surveillance in intact brains and become activated in response to inflammation and neurodegeneration. Microglia have different functions, neuroprotective or neurotoxic, according to aging in patients with PD. The clinical effect of microglia in patients with Alzheimer's disease (AD) is poorly defined. This prospective study was conducted to investigate the clinical effects of microglia according to the aging process in newly diagnosed AD.Methods: We examined 532 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 17 publications
2
28
0
1
Order By: Relevance
“…In the current literature, the common ageing‐related diseases and conditions associated with increased CRP levels include CVD, hypertension, diabetes mellitus, chronic kidney injury, Alzheimer's disease and Parkinson's disease …”
Section: Crp and Ageing‐related Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In the current literature, the common ageing‐related diseases and conditions associated with increased CRP levels include CVD, hypertension, diabetes mellitus, chronic kidney injury, Alzheimer's disease and Parkinson's disease …”
Section: Crp and Ageing‐related Diseasementioning
confidence: 99%
“…C‐reactive protein, an acute phase protein, is primarily produced and secreted by the liver and is an important risk factor associated with ageing‐related diseases including cardiovascular disease (CVD), hypertension, diabetes mellitus, kidney disease and cognitive decline . However, recent studies have also shown that CRP is an important immunologic effector molecule with vital physiological functions .…”
Section: Introductionmentioning
confidence: 99%
“…According to some authors, CRP is a peripheral biomarker that reflects peripheral and central inflammation (and neuroinflammation) (Felger et al 2018). Elevated systemic CRP levels have been noted in numerous conditions associated with peripheral and central neural damage as well as impaired neuroprotection, i.e., Alzheimer's disease (Song et al 2015;Kempuraj et al 2017;Gabin et al 2018), Parkinson's disease (Sawada et al 2015;Umemura et al 2015;Qiu et al 2019), depression (Felger et al 2018), opioid use disorder , or following chimeric antigen receptor T cell (CAR-T) therapy in cancer (Santomasso et al 2018;Wang and Han 2018). To justify our choice of markers, it should also be mentioned that both TNFα and CRP in serum have been evaluated in parkinsonian patients and correlated with motor deficits (Lindqvist et al 2012;Eidson et al 2017).…”
Section: Analytical Methods Reference Bananamentioning
confidence: 99%
“…Similar dispute is also found in levels of CRP. Despite the findings that CRP was decreased in AD patients, a recent study provided opposite results 19,20 .…”
mentioning
confidence: 93%